EVALUATION OF THE CHILD-FRIENDLY SCHOOL POLICY IN CREATING A SAFE AND INCLUSIVE EDUCATIONAL ENVIRONMENT AT MI DARUL HUDA - Silmul Fuady, Ahmad; Al Maddani, Khalid (International Conference on Humanity Education and Society (ICHES), 2025)
This study aims to answer the main question of how the Child-Friendly School policy is implemented at Madrasah Ibtidaiyah Darul Huda, located in a rural area with strong Islamic traditions. The research positions the madrasah as an institution adaptingnational child protection policies within a religious local context. A descriptive qualitative approach was applied through observation, in-depth interviews, and document analysis. Findings indicate that the policy has been socialized throughteacher training, the establishment of a dedicated task force, and the formulation of anti-violence rules. However, implementation faces challenges including varying perceptions among senior teachers regarding non-punitive discipline, limited supporting facilities, and inconsistent parental involvement. The study shows that the success of the policy is determined by the internalization of Islamic values of rahmatan lil ‘alamin, rather than formal regulations alone. This research contributes tounderstanding the dynamics of child protection policy implementation in Islamic educational settings